2019
DOI: 10.1186/s40249-019-0537-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of echinococcosis in Tibet Autonomous Region of China

Abstract: Background The echinococcosis is prevalent in 10 provinces /autonomous region in western and northern China. Epidemiological survey of echinococcosis in China in 2012 showed the average prevalence of four counties in Tibet Autonomous Region (TAR) is 4.23%, much higher than the average prevalence in China (0.24%). It is important to understand the transmission risks and the prevalence of echinococcosis in human and animals in TAR. Methods A stratified and proportionate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 31 publications
3
56
0
2
Order By: Relevance
“…The echinococcosis has been included in the list of 17 neglected tropical diseases by World Health Organization (WHO) [8].China has the highest endemicity of echinococcosis in the world [3,4], and speci cally the Qinghai-Tibet Plateau region of China [4,7]. The pubic health burden is large because the diseases are di cult to treat, requiring complex surgical procedures and long-term high dose antihelminthic treatment [9].And the unique social-cultural background and lifestyle in Tibetan communities adds further di culties to diseases control and prevention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The echinococcosis has been included in the list of 17 neglected tropical diseases by World Health Organization (WHO) [8].China has the highest endemicity of echinococcosis in the world [3,4], and speci cally the Qinghai-Tibet Plateau region of China [4,7]. The pubic health burden is large because the diseases are di cult to treat, requiring complex surgical procedures and long-term high dose antihelminthic treatment [9].And the unique social-cultural background and lifestyle in Tibetan communities adds further di culties to diseases control and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Linzhi has 1 administrative district and 6 counties, which are Bayi District, Gongbujiangda, Milin, Motou, Bomi, Chayu, and Lang County. Among these 7 counties/district, Bayi, Gongbujiangda, Bomi, and Chayuhas reported as co-endemic areas of both CE and AE,while the other 3 counties reported as CE endemic areas [4,7]. The epidemiological survey of echinococcosis in TAR in 2016 reported that the prevalence of echinococcosis in Linzhiwas 1.55%, among which the CE prevalence was 1.34%, the AE prevalencewas 0.20%, and the infection rate of dogs was 7.28% (45/618) [7].…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…As the early phase of infection is generally asymptomatic, patients may remain asymptomatic for years, even permanently. Given the long incubation period (5-20 years), echinococcosis is not easy to be diagnosed in the early stage, and many asymptomatic patients are diagnosed by chance [11][12][13]. Besides, detecting small cystic lesions is also a challenge in imaging diagnosis of echinococcosis.…”
Section: Introductionmentioning
confidence: 99%